Analisis Kebijakan Regionalisasi Rujukan terhadap Jumlah Kunjungan dan Kepuasan Peserta Jaminan Kesehatan Nasional - Amirul Mustofa; Arlina Dewi (JHeS (Journal of Health Studies), 2018)
This research was conducted to know the difference of visit number and satisfaction level before and after referral regionalization policy. The research type is quantitative with cross sectional study approach. This study uses secondary data of JKN participants at the Hospital Bantul District. Data analysis using paired t-test paired test and analysis of variance (Anova). Based on the test of normality's output that visit data and satisfaction are normally distributed. The research data was taken in seven hospitals because it has complete data about JKN participants' satisfaction data in Advanced Health Facility Advanced Facility (FKRTL) before and after the policy was enacted.